A New Validated Stability Indicating RP-HPLC Method for Simultaneous Quantification of Formoterol Fumarate Dihydrate and Mometasone Furoate in Metered Dose Inhalation Aerosol - Prakash Mamillapalli, Surya; Lakshmi Prasanna, Gourabattina; Venkata Subbaiah, B.; Annapurna, N. (Asian Journal of Chemistry, 2021)
Stability indicating reversed phase-HPLC method for simultaneous estimation of mometasone furoate (MAF) and formoterol fumarate (FFD) in metered dose inhalation aerosol (MDI) dosage formulation has been developed and discussed in the present work. The chromatographic separation was achieved using Hypersil ODS column (250 mm × 4.6 mm, 3 μm) using an isocratic separation mode at a flow rate of 1.2 mL/min, column temperature of 50 ºC. The system operates with a mobile phase comprising of solution-A (buffer): Solution-B (acetonitrile) mixed in the ratio of 70:30 %v/v at a UV detection wavelength of 214 nm. Retention times of mometasone furoate and formoterol fumarate found to be about 3 min and 7 min, respectively. All possible degradation products of both compounds were monitored at 214 nm and spectral purity along with % mass balance is assessed using PDA detector. Both analyte were subjected to force degradation studies, found all degradants were resolved from analyte peaks and also other process-related impurities. The proposed method is validated for specificity, linearity, accuracy, precision and robustness as per ICH guidelines and found to be adequate. Method stood to be robust with variation in column temperature, flow rate, pH of buffer and organic content in mobile phase.